plz answer...

Asked by  | 23rd Jun, 2009, 07:29: PM

Expert Answer:

a root of an equation must satisfy the equation, i.e. after substituting the value of the root in place of the variable, we must get,

 LHS=RHS.

so in this case,

 by substuting,x=2/3

we get,

(4a/9)+(14/3)+b=0

i.e.

4a+42+9b=0...(i)

Simly,

 by substituting x = -3

we get,

9a-21+b=0..(ii)

Solving both you can find a and b.

Answered by  | 24th Jun, 2009, 12:33: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.